2020
DOI: 10.2147/oaem.s227750
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Effect of Basic CPR Training on Adults’ Knowledge and Performance in Rural Areas of Iran: A Quasi-Experimental Study</p>

Abstract: Introduction: Cardiac arrest happening outside the hospital, specifically in rural regions that are more distant from health centers, is a crucial issue in the health of individuals in those regions. Therefore, the ability of residents in those regions to do cardiopulmonary resuscitation (CPR) is very important in preventing death among people. This study aimed at determining the effect of basic CPR training on the adults' knowledge and performance in rural areas. Methodology: This quasi-experimental study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 34 publications
1
8
0
2
Order By: Relevance
“…Previous BLS training was significantly associated with higher knowledge scores (p=0.0001). This aligns with experimental study findings from Iran that indicated higher knowledge after basic BLS training [23]. Though the association of gender with BLS knowledge and skills was not well studied among schoolteachers, we found that the male gender was significantly associated with higher knowledge than the female gender (95% C.I.…”
Section: Discussionsupporting
confidence: 90%
“…Previous BLS training was significantly associated with higher knowledge scores (p=0.0001). This aligns with experimental study findings from Iran that indicated higher knowledge after basic BLS training [23]. Though the association of gender with BLS knowledge and skills was not well studied among schoolteachers, we found that the male gender was significantly associated with higher knowledge than the female gender (95% C.I.…”
Section: Discussionsupporting
confidence: 90%
“…[ 22 ] Previous studies on teachers before and after BLS training found an improvement in BLS sequence and quality of chest compression after training. [ 16 23 ]…”
Section: Discussionmentioning
confidence: 99%
“…The same as above, we also examine the within-group comparisons for the pre-test and posttest scores of entrepreneurial mindset sub-scales. Referring to previous studies (e.g., Ko & Park, 2018;Khademian et al, 2020;Kivelä et al, 2020;Tinôco et al, 2021;Girard et al, 2023), the expected findings for those within-group comparisons are that the entrepreneurial mindset sub-scales will increase in the treatment group but they will not change in the control group (see Appendix 1). Accordingly, we also use the scripts of directional research hypotheses (Tuckman & Harper, 2012;Cho & Abe, 2013;Creswell & Creswell, 2018;Babbie, 2021), and the wordings are as follows:…”
Section: Research Hypothesesmentioning
confidence: 74%
“…Before the experiential learning program started, the five sub-scales (i.e., ELAM, IMPLM, EM_AO, EM_AT, and EM_CR) were the same between the undergraduate students who participated in the program and those who did not participated in the program (i.e., H1a, H1b, H1c, H1e, and H1f were supported). The findings demonstrated the homogeneity in the pre-intervention (see Ko & Park, 2018;Khademian et al, 2020;Kivelä et al, 2020;Tinôco et al, 2021;Girard et al, 2023). However, before the experiential learning program started, the undergraduate students who involved in the experiential learning program had a lower EM_RP than those who did not involve in the program (i.e., H1d was not supported).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation